On the 100th birthday of outstanding scientist Ostap Stepanovych Parasyuk (20.12.1921 – 22.11.2007): Ostap Stepanovich Parasyuk - Zagorodnii , A. G.; Samoilenko , A. M.; Bugrov, V. A.; Mel’nyk, V. P.; Zgurovs’kyi , M. Z.; Stricha , M. V.; Virchenko , N. O. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
A short essay on the life and scientific work of the Ukrainian scientist of world fame (mathematician) Academician Ostap Stepanovych Parasyuk is given.